2020
DOI: 10.1002/tpg2.20048
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating forest tree breeding by integrating genomic selection and greenhouse phenotyping

Abstract: Breeding forest species can be a costly and slow process because of the extensive areas needed for field trials and the long periods (e.g., five years) that are required to measure economically and environmentally relevant phenotypes (e.g., adult plant biomass or plant height). Genomic selection (GS) and indirect selection using early phenotypes (e.g., phenotypes collected in greenhouse conditions) are two ways by which tree breeding can be accelerated. These approaches can both reduce the costs of field-testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The study showed a moderate correlation (0.39-0.42) between greenhouse height measurements at weeks 13 and 15 and field measurements at years 3-5. By combining multiple greenhouse phenotypes into a selection index, a relative efficiency of~0.48 was achieved, which is comparable with the results of GS models based on field phenotypes only [71].…”
Section: Importance Of Age-related Phenotypingsupporting
confidence: 66%
See 1 more Smart Citation
“…The study showed a moderate correlation (0.39-0.42) between greenhouse height measurements at weeks 13 and 15 and field measurements at years 3-5. By combining multiple greenhouse phenotypes into a selection index, a relative efficiency of~0.48 was achieved, which is comparable with the results of GS models based on field phenotypes only [71].…”
Section: Importance Of Age-related Phenotypingsupporting
confidence: 66%
“…On the other hand, quite opposite results have been obtained lately. In order to reduce the breeding cycle, Alves et al [71] integrated indirect phenotypic selection based on greenhouse phenotypes with traditional GS. Plants of the same genotypes of Populus deltoides were grown in the field and in a greenhouse, with plant height measurements collected from week 1 to 15 in the greenhouse and at years 1 to 5 in the field.…”
Section: Importance Of Age-related Phenotypingmentioning
confidence: 99%
“…This approach would require the integration of nursery and field phenotypes to develop a more accurate GS model. Such an approach was demonstrated in Populus deltoids for tree height to accelerating its breeding strategies (Alves et al, 2020). The proposed GS approach in this involves challenging potted families with L. invasa and scoring Lepto tolerance 6 months after potting and then advancing the most tolerant individuals across families for BotryoTera tolerance scoring at 12 months after potting.…”
Section: Proposed Selection Strategies For Diameter Growth and Lepto And Botryotera Tolerancementioning
confidence: 99%
“…Well studied benefits of GS for forest tree breeding programs, in increasing genetic gains by shortening generation intervals and increasing prediction accuracies (Grattapaglia and Resende, 2011 ; Iwata et al, 2011 ; Grattapaglia et al, 2018 ), and combining the methodology with clonal propagation and somatic embryo-genesis (Li and Dungey, 2018 ), can be utilized in the Swedish conifer breeding programs to decrease generation intervals. Another advantage of GS in forest tree breeding is the possibility to increase the selection intensities and getting larger genetic gains, by reducing the breeding cycle through skipping or reducing the field-testing periods (Harfouche et al, 2012 ; Isik, 2014 ; Grattapaglia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%